Blastocystis subtype 5: Predominant subtype on pig farms, Thailand. Issue 6 (December 2018) - Pintong, Ai-rada; Sunyanusin, Suparat; Prasertbun, Rapeepan; Mahittikorn, Aongart; Mori, Hirotake; Changbunjong, Tanasak; Komalamisra, Chalit; Sukthana, Yaowalark; Popruk, Supaluk
Abstract: Blastocystis is a unicellular protist most commonly detected in humans and a variety of animals. The predominant mode of its transmission is the fecal–oral route, but its zoonotic potential is not completely understood. The objective of this study was to determine the presence and genetic diversity of Blastocystis on pig farms in Nakhon Pathom Province, Central Thailand. A total of 154 human and 90 pig stool samples were collected and analyzed. Nested PCR detected Blastocystis in 35.55% of the pig samples and 6.49% of the human samples. Subtyping based on regions of the small-subunit ribosomal RNA (SSU rRNA) gene identified three Blastocystis subtypes in pigs and humans: ST1, ST3, and ST5. Blastocystis ST5 was the predominant subtype, followed by ST1 and then ST3. All the sequences from the Blastocystis -positive samples from both pigs and humans were closely related. This study reveals a possibility of low host specificity of Blastocystis STs (ST1, ST3 and ST5) on pig farms in Thailand. We tentatively suggest that close contact with or exposure to pig stools may be a significant source of Blastocystis detected in pig handlers. Further studies are required to confirm the zoonotic transmission of this organism in Thailand, because pigs may play an important role in the transmission of Blastocystis . Graphical abstract: Unlabelled Image Highlights: High percentages of Blastocystis infection in pigs Blastocystis ST5 was the predominant subtype in both humans and pigs. A possibility of low host specificity of Blastocystis STs (ST1, ST3 and ST5) on pig farms in Thailand